Some methodological issues of the history of science and technology - Griffen, Leonid; Ryzheva, Nadiia; Nefodov, Dmytro; Hryashchevskaya, Lyudmila (Ìstorìâ nauki ì tehnìki (Kiïv. Online), 2022)
Further development of the history of science and technology requires the solution of a number of methodological problems. The article considers the object and subject of the history of science and technology, its place in the system of sciences. Today, more and more people are turning to the factors that determine the interaction of the society with the environment (productive forces of the society), to study which in the historical aspect and called a special scientific discipline - the history of science and technology. The society as an object of knowledge is a biological organism of the highest level of organization of “cells” - individuals. It exists and develops in the environment due to its own entropy. The society organizes this removal through a specialized subsystem formed on the basis of technical devices – “technosphere”. The success of such a process is ensured (through the information field) by another subsystem - the “noosphere”. These subsystems include both ideal and material objects. The composition and development of the technosphere and noosphere are considered in the article. It is shown that the functioning of the technosphere is based on its interaction with the noosphere, which provides information about the environment and controls the effectiveness of interaction with it. It is formed by combining the mental structures of individuals through sign systems. The production process that ensures the functioning of the society begins with the noosphere, which through individual consciousness controls the actions of each individual, who through the means of production (technosphere) interacts with the natural environment. However, the gradual development of productive forces leads at some point to the fact that the information needed by the individual to perform all necessary actions for the benefit of the society, ceases to fit in his individual consciousness. As a result, there is a new social phenomenon - the social division of labor. On the one hand, there is a division of technological operations between different performers (technological division of labor), and on the other - the selection of individuals who coordinate the efforts of performers and receive impetus to work not directly from public consciousness, but through these persons (social division of labor). As a result, there are special relationships between individuals and their groups (production relations), and thus begins the class period of human existence. And it will continue until the development of productive forces leads to the full transfer of all technological functions to technical systems, which due to the direct interaction of the noosphere and technosphere will put an end to the social division of labor. However, the development of productive forces is also accompanied by the acceleration of entropy in the environment of mankind - the geobiosphere of the planet Earth, which is gradually making it less and less suitable for life. The cardinal solution to the problem is the prospect of humanity entering infinite space.